2021
DOI: 10.5114/amsad.2021.105390
|View full text |Cite
|
Sign up to set email alerts
|

Pulse wave velocity, carotid intima media thickness and flow-mediated dilation in Takayasu arteritis: a systematic review

Abstract: Introduction: Takayasu arteritis (TA) is a chronic vasculitis associated with an increased cardiovascular risk. The measurement of pulse wave velocity (PWV), carotid artery intima-media thickness (CIMT) and flow-mediated dilatation (FMD) are generally used for evaluating the cardiovascular risk. The application of these measurements to TA patients remains undetermined. Material and methods: Clinical studies that reported the PWV, CIMT and FMD levels in TA patients, which were published prior to 2021, were summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…The impact of prednisone treatment was also shown, with lower values of FMD in patients with TAK who underwent treatment. No correlation was seen between FMD and disease duration or activity (159).…”
Section: Papers II and Iv (Tak And Sle)mentioning
confidence: 75%
“…The impact of prednisone treatment was also shown, with lower values of FMD in patients with TAK who underwent treatment. No correlation was seen between FMD and disease duration or activity (159).…”
Section: Papers II and Iv (Tak And Sle)mentioning
confidence: 75%
“…They concluded that TAK patients demonstrated affected values in all these measured modalities. However, all included studies had a small number of patients, and none of the studies investigated the change in PWV, IMT and FMD during follow-up ( Watanabe et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that TAK patients demonstrated affected values in all these measured modalities. However, all included studies had a small number of patients, and none of the studies investigated the change in PWV, IMT and FMD during followup (Watanabe et al, 2021).…”
Section: Discussionmentioning
confidence: 99%